Combined method for acoustic cavitation research - A. V. Kotukhov; V. S. Gavrilyuk; V. S. Minchuk; N. V. Dezhkunov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
At present, the field of applications of powerful ultrasound is expanding intensively, and the improvement of equipment and technological processes continues. With that, the key factor in the effect of ultrasonic vibrations on processes in liquids and liquid-like media is cavitation, i.e. the phenomenon of formation, pulsation and collapse of gas microbubbles under the influence of variable pressure. The widespread introduction of promising ultrasound technologies is largely constrained by the fact that the patterns of cavitation generation are not well understood, and the data known in the literature are contradictory and are characterized by low reproducibility. This paper describes an innovative method for studying ultrasonic cavitation. In order to increase the reproducibility of the results and the reliability of the conclusions about the correlation of various cavitation effects, it is proposed to register simultaneously the parameters characterizing these effects. An installation designed to implement this method has been developed and tested. The installation provides the ability to register the full output signal of the hydrophone, the intensity of the glow generated in the cavitation region - sound luminescence, the cavitation noise spectrum and its individual components. Technical characteristics of the installation allow you to adjust the rate of development of the cavitation region by varying the duration and period of the ultrasound pulses. It is possible to conduct experiments both in low-frequency (LF) and high-frequency (HF) fields as well as in interacting HF and LF ultrasonic fields. During the testing of the installation, the results were obtained that are of considerable interest from the point of view of refining the ideas about the mechanism for generating cavitation effects. It was found that preliminary treatment of the liquid in an ultrasonic field with the aim of its degassing for 15–20 min provides a significant increase in the reproducibility of measurements, especially for liquids with a high gas content. Based on a comparison of the time dependences of the signals of the cavitation sensor and the photomultiplier output, the characteristic stages of the development of the cavitation region are distinguished, which differ in the dynamics of the development of the cavitation region and in the composition of the cavitation noise spectra recorded.